2018
DOI: 10.1002/celc.201800430
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Fabrication of Carbon Nanotubes‐Decorated Sn4P3 as a 3D Porous Intertwined Scaffold for Lithium‐Ion Batteries

Abstract: Through a one‐step solvothermal approach, the carbon nanotubes‐decorated Sn4P3 nanohybrid with intertwined scaffold structure and enhanced electroconductivity is successfully composed as anode material in lithium‐ion batteries, using nontoxic red phosphorus and SnCl2 as starting materials. The special architecture of the nanohybrid exhibits more active sites for lithium ions and buffers the huge volume expansion. When used as anodes in lithium‐ion batteries, the material shows superior electrochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The microstructure evolution during the lithiation/delithiation process of Sn x P y /RGO electrodes is shown in Figure 5h. As reported in the literature, 15,16,38 the graphene coating structure can effectively avoid the agglomeration of Sn nanoparticles, but with the progress of the long cycling, the Sn nanoparticles could still be agglomerated seriously and the structure would be broken, while the Sn x P y / RGO electrode material can effectively prevent the agglomeration of Sn nanoparticles due to the synergistic enhancement effect of multiple phases, thereby maintaining the structural stability.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The microstructure evolution during the lithiation/delithiation process of Sn x P y /RGO electrodes is shown in Figure 5h. As reported in the literature, 15,16,38 the graphene coating structure can effectively avoid the agglomeration of Sn nanoparticles, but with the progress of the long cycling, the Sn nanoparticles could still be agglomerated seriously and the structure would be broken, while the Sn x P y / RGO electrode material can effectively prevent the agglomeration of Sn nanoparticles due to the synergistic enhancement effect of multiple phases, thereby maintaining the structural stability.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The cycling performance of the Sn x P y /RGO electrode at 2000 mA g –1 is shown in Figure e; impressively, the electrode can still deliver a reversible capacity of 713.5 mA h g –1 even after 1400 cycles, and the CE is stable at around 100%. The rate capability and cycling performance for Sn-based phosphide anode materials are compared in Figure f and Table S2, ,,,, and it can be concluded that the obtained Sn x P y /RGO electrode has the most excellent rate performance and the most stable long-cycle performance. The outstanding electrochemical performance for the Sn x P y /RGO composite, especially the properties of high capacity and ultra-stable long-term cycling, are closely related to the synergistic effect of multiple phases and the interaction between Sn x P y and RGO.…”
Section: Resultsmentioning
confidence: 98%
“…However, a mass of smaller nanosized Sn 4 P 3 particles is displayed on the surface of the electrodes, which is quite distinct from those after 5 and 150 cycles. The refinement of Sn 4 P 3 nanoparticles during the charge/discharge cycles would result in more active sites and a solid contact between the Sn 4 P 3 nanoparticles and MXenes, 17 which is favorable for lithium accommodation and charge transfer. Furthermore, the EIS spectra of SnO 2 @MXene-5 and Sn 4 P 3 @ MXene-5 electrodes after 5, 150, 250, and 300 cycles are also presented in Figure S11.…”
Section: Resultsmentioning
confidence: 99%
“…However, the large volume expansion (up to 353%) upon Li insertion/extraction and the low electrical conductivity give rise to particle pulverization and high reaction irreversibility of Sn 4 P 3 anodes, leading to fading of the permanent capacity and hence the rapid deterioration of battery performance. To address these issues, carbon-based materials such as porous carbon, carbon nanotubes, carbon fibers, and graphene , have been widely introduced as a matrix to construct Sn 4 P 3 /carbon composites at the nanoscale because they can not only accommodate the expansion strain like a cushion but also accelerate the ion transport in the composites . However, the porous and low density features of carbon-based materials would decrease the volumetric energy density and initial Coulombic efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Sn 4 P 3 decorated on carbon nanotube scaffolds were synthesized to deliver 480 mA h g −1 at 2 A g −1 as LIB anodes. 27 However, in most carbon/Sn 4 P 3 structures, Sn 4 P 3 particles were only attached on the surfaces of carbon materials, lacking robust carbon coating or encapsulation for volume change buffering during cycling. In addition, in typical Sn 4 P 3 / carbon core−shell structures, the encapsulated particle size of Sn 4 P 3 is always hundreds of nanometers, which is not beneficial for fast charging.…”
Section: Introductionmentioning
confidence: 99%